Images in Sarcoidosis: new section of our Journal - Baughman, Robert P.; Caminati, Antonella; Ravaglia, Claudia; Richeldi, Luca; Rottoli, Paola; Tomassetti, Sara; Vancheri, Carlo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
.